MOTIVATION AND VALENCY AS THE MAIN CONTRIBUTORS TO THE EXTENSION OF THE SEMANTIC FIELD OF ’BEHAVIOUR ’ - Durdona Tosheva Dilmurodovna; Albina Bazarbaeva (TADQIQOTLAR.UZ, 2024)
In this article, the author scientifically substantiates the contribution and role of assimilation in managing the behavioral semantic field of motivation and valence. Uzbek and World researchers who have conducted scientific work on the following topic will discuss their scientific work. Brings up the imperial research he conducted, works common.